Ecotoxicology - Shugart, Lee R.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Ecotoxicology is an international journal devoted to the publication of fundamental research on the effects of toxic chemicals on populations, communities and terrestrial, freshwater and marine ecosystems. It aims to elucidate mechanisms and processes whereby chemicals exert their effects on ecosystems and the impact caused at the population or community level. The journal is not biased with respect to taxon or biome, and papers that indicate possible new approaches to regulation and control of toxic chemicals and those aiding in formulating ways of conserving threatened species are particularly welcome. Studies on individuals should demonstrate linkage to population effects in clear and quantitative ways. Laboratory studies must show a clear linkage to specific field situations. The journal includes not only original research papers but technical notes and review articles, both invited and submitted. A strong, broadly based editorial board ensures as wide an international coverage as possible.
Keywords: Ecology; Environment; Environmental management; Ecotoxicology; Environment, general; Ecotoxicology; Ecology; Environmental Management